Primary structure of rabbit 18S ribosomal RNA determined by direct RNA sequence analysis. - Connaughton, J F (1984)
The primary structure of rabbit 18S ribosomal RNA was determined by nucleotide sequence analysis of the RNA directly. The rabbit rRNA was specifically cleaved with T1 ribonuclease, as well as with E. coli RNase H using a Pst 1 DNA linker to generate a specific set of overlapping fragments spanning the entire length of the molecule. Both intact and fragmented 18S rRNA were end-labeled with [32P], base-specifically cleaved enzymatically and chemically and nucleotide sequences determined from long polyacrylamide sequencing gels run in formamide. This approach permitted the detection of both cistron heterogeneities and modified bases. Specific nucleotide sequences within E. coli 16S rRNA previously implicated in polyribosome function, tRNA binding, and subunit association are also conserved within the rabbit 18S rRNA. This conservation suggests the likelihood that these regions have similar functions within the eukaryotic 40S subunit.